2011
DOI: 10.1007/s11782-010-0129-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of natural disaster on absenteeism, job satisfaction, and job performance of survival employees: An empirical study of the survivors in Wenchuan Earthquake

Abstract: Natural disasters cause serious damage to businesses in the stricken areas and greatly affect survivors' psychology and behaviors. Based on data from 206 survival employees in 33 affected firms in Wenchuan Earthquake, this study analyzes the impact of natural disaster on absenteeism, job satisfaction, and job performance of survival employees. Results indicate that after the earthquake, survival employees' absenteeism and job satisfaction (including intrinsic, extrinsic, and general job satisfaction) decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
0
17
0
2
Order By: Relevance
“…Job security refers to "employee's expectations about the stability and longevity of their job in an organization" (Lu et al, 2017, p. 30). Research shows that natural disasters and public health crises impose negative economic impacts (Qin & Jiang, 2011;Mastroianni, 2009). Following the Wenchaun Earthquake in China, private enterprises suffered major economic damage (Qin & Jiang, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Job security refers to "employee's expectations about the stability and longevity of their job in an organization" (Lu et al, 2017, p. 30). Research shows that natural disasters and public health crises impose negative economic impacts (Qin & Jiang, 2011;Mastroianni, 2009). Following the Wenchaun Earthquake in China, private enterprises suffered major economic damage (Qin & Jiang, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research shows that natural disasters and public health crises impose negative economic impacts (Qin & Jiang, 2011;Mastroianni, 2009). Following the Wenchaun Earthquake in China, private enterprises suffered major economic damage (Qin & Jiang, 2011). Data from survivors of the earthquake revealed that their sense of job insecurity significantly increased (Qin & Jiang, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the report from hospitals and public health centers, a substantial percentage of personnel’s absence occurs during incidents like pandemics and terrorist cases such as chemical, biological and nuclear incidents [ 4 , 6 ]. Also, some literature indicated that after natural disasters absenteeism and job satisfaction significantly have decreased [ 7 ].…”
Section: Introductionmentioning
confidence: 99%